Studi Karakteristik Beton Porous Dengan Menggunakan Agregat Sungai Maulu - Suryanti Rapang Tonapa; Lisa Febriani; Desi Sandy; Pebrinar Riani Sangle; Abigail Mangiri Massolo (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
Local aggregate management in a region must be optimized by considering the need for materials that provide sustainable green solutions. Materials sourced from the Maulu River have not been widely explored scientifically and optimally utilized in concrete technology. This research offers novelty through the use of local aggregates originating from the Maulu River as a constituent material for porous concrete and an analysis of the relationship between aggregate characteristics and the physical and mechanical properties of concrete, including pore volume, permeability, and compressive strength. By setting the aggregate dimension number 8, which is in the range of 2.38 mm to 9.5 mm. This study aims to identify the characteristics of porous concrete based on the constituent materials from the Maulu River in Tana Toraja Regency. The duration of the research, which took place from October to December 2024, by applying the ACI 522R-10 porous concrete mix planning, as well as analyzing the characteristics of porous concrete such as pore volume, permeability, and compressive strength. The results of the study showed that the average void ratio was 18.453%, the average permeability was 5.964 mm/second and the average compressive strength at the ages of 7, 21, and 28 days was 6.04 MPa, 7.30 MPa, and 8.32 MPa. By referring to the qualified characteristics, the results of this study are expected to provide a sustainable green connectivity solution for the people of the Sungai Maulu area.